Efforts to Improve Students’ Critical Thinking Skills in Primary Education Fundamental Class through Group Investigation Model - Chairunnisa, Connie (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
This study aimed to describe the application of Group Investigation Model (GIM) to improve students’ comprehension of subject concepts and their critical thinking skills and to understand the challenges faced by lecturers while practicing GIM in the classroom. The research approach used was a qualitative method of description involving 21 students who took the course of the Foundation of Education in the Education Administration study program at Muhammadiyah University of Prof.Dr.Hamka (Uhamka), Jakarta , Indonesia, in the odd semester 2019/2020. Data were collected through tests, observations, interviews, questionnaires, and documents. The application of GIM in the Education Foundation class can improve students’ critical thinking skills. The study findings suggested that the average student’s grades improved on formative tests. In using GIM there are several challenges that include aspects of learning and outside learning. This study suggests: (1) prior to implementing this model, careful preparation is needed, especially in the learning process so as to encourage students to actively think and ask questions. 2) In implementing this GIM, it is necessary to have guidance and motivation from the lecturer. (3) The implementation of this GIM can be successful if the stages one and two have been agreed and determined.